QUALITY AND GROUNDWATER FLOW AT DEGAN, BANJARARUM, WEST PROGO - Dianto Isnawan; . . T. Listyani R.A. (KURVATEK, 2019)
This research is a hydrogeological survey activity with the aim to determine the quality and pattern of groundwater flow in the Degan and surrounding areas, Banjararum Village, Kalibawang, West Progo District. The research method is carried out by hydrogeological surveys to collect groundwater data and groundwater quality in the form of pH, TDS and EC. The research area is included in the Dome of the Kulon Progo physiography, where this area is a non CAT area. The geomorphology of the study area in the north and west is dominated by relatively coarse landscapes forming hills, while in the central, eastern and southern parts it is a weak wavy landscape to the plains. The results showed that shallow groundwater depth of 1.2 - 10.8 m (under surface). The pattern of groundwater flow is to the east / southeast, with boundary conditions H5 and V1. Groundwater aquifers are composed of colluvium deposits and weathered  - medium weathered rock. The pH value of water in the study area ranges from 6.7 -7.1; TDS is 165 - 901 ppm, while EC ranges from 187 - 1240 µS / cm. Thus, groundwater in the Degan area is neutral and tasteless.